Keunggulan Podcast dalam Mengedukasi Masyarakat terhadap Program Vaksinasi Covid-19 - Shiddiq Sugiono (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2021)
Every person and organization must know the advantages of podcast so they can maximize the effectiveness of the communication strategy for the Covid-19 vaccination program. Podcasts are media content that gets public attention during a pandemic. Podcasts needs to be maximized by every stakeholder because during the pandemic there is a lot of misinformation that has the potential to hinder the success of the vaccination program. The delivery of health information is one of the efforts to improve the quality of public health. This study aims to provide the advantages of podcasts in providing public understanding of Covid-19 vaccination. The method in this study is literature review with qualitative approach. The literature sources were obtained from Google Scholar with the keywords podcast, vaccine, and covid-19. The results of the synthesis were analyzed using a qualitative descriptive technique. The results state that podcasts have 4 advantages that can be used as opportunities to communicate understanding about vaccination, namely: presenting experts, easy access to information, advantages of audio-type content and user generated content/UGC. By presenting credible sources, podcast content is expected to be able to increase the validity of the information. Podcasts can be made by anyone, not only individuals but also government institutions, educational institutions to even the health industry. Podcasts were considered capable of playing a role in improving the quality of public health because various stakeholders took the initiative to communicate vaccinations. This study also builds a conceptual framework of podcast advantages in supporting Covid-19 vaccination education.